(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study examines how contemporary Indian poets utilize their art as a powerful means of social and political protest. In a nation characterized by a complex interplay of cultural identities, historical traumas, and systemic inequalities, modern Indian poetry has emerged as a critical platform for addressing pressing issues such as caste discrimination, gender inequality, environmental degradation, and political oppression. The paper highlights the works of influential poets like Agha Shahid Ali, Kamala Das, Meena Kandasamy, Arun Kolatkar, and Gauri Maithri, each of whom brings a unique perspective to their craft. Through their poetry, these voices articulate the pain, resilience, and struggles of marginalized communities, transforming personal narratives into collective experiences of resistance.